REAKSI PASAR SAHAM INDONESIA TERHADAP PUBLIKASI INFORMASI LAPORAN KEUANGAN PERUSAHAAN - ALDO HUBERT; Ratih Handayani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research was to examine the Indonesian stock market reaction to the publication of the company financial statement. Using some variabels of financial ratios (return on asset, debt to equity ratio, price to book value, total asset turnover, price to earnings ratio, and earnings per share) to test the hyphothesis, the test was examined. The objects of this research are manufacturing companies that listed in Indonesia Stock Exchange during 2017-2020. Samples were selected using purposive sampling method and there are 46 companies that met the criteria. Hypothesis was analyzed using multiple regression method.The results shows that return on asset, debt to equity ratio, price to book value, total asset turnover, firm size, and earnings per share have no influence to stock return. On the other side, price to earnings ratio have influence to stock return. The expectation of growth in earning became one of the most interesting for investor in stock market. Capital market efficiency implies that information is fully impounded in securities prices.